The Protection of Traditional Knowledge of Medicinal Herbs for Just Health and Welfare Access for the Traditional Communities: A Comparison between India and Indonesia - Yenny Eta Widyanti; Rahmi Jened; Nurul Barizah (Institute of Medico-legal Publications Pvt Ltd, 2022)
The purpose of this study is to identify a model in the protection of traditional knowledge (TK) of medicinal herbs by adopting a comprehensive protection instrument, comprising positive and defensive protection. Based on the regulation of TK in international conventions and the national laws, the best practice for the protection of TK of medicinal herbs is by implementing a sui generis regulation that stems from the principle of justice in fulfilling the traditional communities’ rights over access to health and welfare.